Optimisation of natural sweeteners for sugar reduction in chocolate flavoured milk and their impact on sensory attributes. (April 2021) - Mahato, Dipendra Kumar; Keast, Russell; Liem, Djin Gie; Russell, Catherine Georgina; Cicerale, Sara; Gamlath, Shirani
Abstract: The possibility of achieving a 50% of added sugar reduction in chocolate milk using natural non-nutritive sweeteners, namely stevia and monk fruit extract was studied and optimised using response surface methodology. Variables were chosen as stevia sweetener (5–100 ppm) and monk fruit extract (50–100 ppm) based on preliminary trials. Sensory attributes (overall liking, appearance, aroma, sweetness, mouthfeel and aftertaste) were taken as the responses. The process was optimised with a combination of 56.27 ppm of stevia sweetener and 81.90 ppm of monk fruit extract with sensory attributes of 6.78, 6.47, 6.31, 6.47, 6.45 and 6.33, respectively for overall liking, appearance, aroma, sweetness, mouthfeel and aftertaste. Use of the two selected sweeteners in combination resulted in sweetness synergy and the bitter and metallic aftertastes of stevia were masked by the monk fruit extract and helped enhance the overall sensory attributes of the product compared with the control.